EFFICIENT DEVELOPMENT OF PROGRESSIVELY ENHANCED WEB APPLICATIONS BY SHARING PRESENTATION AND BUSINESS LOGIC BETWEEN SERVER AND CLIENT - AST, MARKUS; WILD, STEFAN; GAEDKE, MARTIN (Journal of Web Engineering, 2014)
A Web application's codebase is typically divided into a server side and a client side with essential functionalities being implemented twice, such as validation or rendering. While developers can choose from a rich set of programming languages to implement a Web application's server side, they are bound to JavaScript for the client side. Recent developments like Node.js allow using JavaScript in a simple and ecient way also on the server side, but lack oering a common codebase for the entire Web application. In this article, we present the SWAC approach that aims at reducing development eorts and minimizing coding errors in order to make creating Web applications more eciently. Based on our approach, we created the SWAC framework. It enables establishing a uni edWeb application codebase that provides both dynamic functionality and progressive enhancement by taking characteristic dierences between server and client into account.